EVALUASI JUMLAH TENAGA KERJA DALAM KONSTRUKSI MENGHADAPI ERA NEW NORMAL - Putrianti, Pratika Riris (Jurnal Riset Rekayasa Sipil, 2021)
The impact of Covid-19 on the implementation of construction services includes budget cuts, delays in project completion, increased implementation costs, potential for construction disputes. In the era of "New Normal”, it is done with the condition that Covid-19 transmission has been controlled by Public Health and the capacity of the health system is able to identify, isolate, test, track contracts and quarantine. In the era of "New Normal" reduce the risk of outbreaks by strict regulation of places that have high vulnerability, prevention at work is implemented, the risk of the spread of imported cased can be controlled, and people take part and be involved in the transition. The design of "New Normal" in terms of Construction can be said as "Construction Adaptation" in which the implementation of construction services that is safe, effective, and efficient to accelerate development while still implementing health protocols. The protocols that should be implemented include: procurement protocols based on online and minimizing face-to-face, work implementation protocols using masks and physical distancing and contract adjustment protocols with contract flexibility to accommodate field conditions. Construction survival strategies in the "New Normal" era, namely: digitizing by optimizing the use of Building Information Modeling (BIM), specialization with a focus on specific expertise, industrialization with modular and precast buildings increasing work productivity, building supply chains with vendor management system, adaptation by absorbing concepts new design and new innovation, trust communication.